2018
DOI: 10.3892/etm.2018.6986
|View full text |Cite
|
Sign up to set email alerts
|

Significance and impact of dietary factors on systemic lupus erythematosus pathogenesis (Review)

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease of unknown etiology, although its mechanisms involve genetic, epigenetic and environmental risk factors. Considering that SLE pathogenesis is yet to be explored, recent studies aimed to investigate the impact of diet, in terms of triggering or altering the course of the disease. To study the impact of diet on SLE pathogenesis, we conducted a search on Pubmed using the keywords 'diet and autoimmune diseases', 'diet and lupus', 'caloric restriction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 47 publications
4
57
0
3
Order By: Relevance
“…The relationship between dietary sugar intake and autoimmunity has not been previously examined but prior studies have indicated that dietary factors play a key role in various autoimmune inflammatory diseases such as rheumatoid arthritis or inflammatory bowel disease [6,[30][31][32]. Moreover, in agreement with our results, recently published research concluded that, in patients with SLE, a good diet can contribute to increasing the period of remission, preventing the adverse effects of medications, and improving the physical and mental well-being of patients [7]. Thus, dietary therapy has now been recognised as a promising approach to treating SLE, owing to both its potential prophylactic effects and its contribution to reducing co-morbidities and improving quality of life in these individuals [33].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The relationship between dietary sugar intake and autoimmunity has not been previously examined but prior studies have indicated that dietary factors play a key role in various autoimmune inflammatory diseases such as rheumatoid arthritis or inflammatory bowel disease [6,[30][31][32]. Moreover, in agreement with our results, recently published research concluded that, in patients with SLE, a good diet can contribute to increasing the period of remission, preventing the adverse effects of medications, and improving the physical and mental well-being of patients [7]. Thus, dietary therapy has now been recognised as a promising approach to treating SLE, owing to both its potential prophylactic effects and its contribution to reducing co-morbidities and improving quality of life in these individuals [33].…”
Section: Discussionsupporting
confidence: 91%
“…Diet has been closely associated with inflammatory autoimmune diseases and is among the modifiable factors related to them [5]. In fact, previous studies have established nutrients as influential factors in inflammatory autoimmune diseases such as SLE or rheumatoid arthritis [6,7]. However, no conclusive associations have yet been consistently established and therefore, the links between diet and SLE remain elusive and intriguing.…”
Section: Introductionmentioning
confidence: 99%
“…Compound of Mediterranean diet and pharmacological treatment decrease the disease activity and improve quality of life in patients with autoimmune disorders such as rheumatoid arthritis and SLE [79,80]. Specifically, beneficial effects of the Mediterranean diet on prevention, treatment, reducing symptoms of pain, and enhancing physical activity in patients with rheumatoid arthritis were observed [79].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…50,51 Conversely, a recent review reports that they regulate levels of total cholesterol, LDL-C, and TG: especially at the ratio of 3:1 for EPA and DHA. 52 Currently, the use of omega-3 PUFAs appears to be limited to the regulation of TG levels. In the recent recommendations from the American Heart Association (AHA), prescription of omega-3PUFAs at a dose of 4 g/d has consistently resulted in significant reductions in TG levels in patients with HTG or VHTG.…”
Section: Omega-3 Pufas and Their Potential Therapeutic Role In Nephromentioning
confidence: 99%